SAT0494 Protein Intake and Body Composition Relationship in A Rheumatic Patient Population. (10th June 2014) - Fernandes, S.; Borges, J.; Gonçalves, I.; Cardoso, A.; Fernandes, R.; Simão, R.; Vila, I.; Pires, G.; Barcelos, F.; Cunha-Miranda, L.; Santos, H.; Leitão, R.; et al.
Abstract : Background: The relationship between protein dietary intake and Bone Mass Index (BMI) is controversial. Hyperproteic diet increases urinary calcium excretion but without obvious impact in Osteoporosis (OP). Sarcopenia in the elderly may be associated with low protein diet. High BMI and with high fat content was considered a protective factor for OP but it may be related to vitamin D deficiency and subclinical hyperparathyroidism. Objectives: This study aims to evaluate the relationship between protein diet intake, BMI and and parathyroid hormone (PTH) levels. Methods: A questionnaire on dietary protein intake was applied to patients at a Rheumatology clinic during 4 non-consecutive weeks from July to September 2013. Nutritional evaluation included body composition (InBody 720). Clinical data collected included: fall occurrence; history of clinical and/or radiologic vertebral fractures; total serum protein, albumin, inorganic phosphate, calcium, PTH, vitamin D and calcium urinary excretion levels and neck/lumbar densitometry. Descriptive statistics, Mann-Whitney, Kruskal-Wallis, Qui-Square and Spearman correlation were applied for a significance of p<0, 05 . Results: 189 subjects were enrolled, 88% female, mean age 58 years, mean BMI 27kg/m 2 (low weight in 1, 7%, normal in 33, 1%, overweight in 37, 7% and obesity in 27, 6%). Regarding protein intake, 66, 7% drunk milk >5 times/week and 22, 2% >2 glasses/day; 61, 3% of the patients consumed yogurt 1-3 times/day and 20, 6% <1/week; 44% consumed cheese once a day. Lean and fatty fish were consumed weekly in 75% of the subjects and canned fish in up to 86%. Codfish and eggs consumption varied between 1 to 4 times/week in 68% and 77%, respectively. Red meat ingestion was: 2-4 times/week in 51%, <3 times/month in 27%. We found an association between weight (r=-0, 131;p=0, 043), body fat content (r=-0, 174;p=0, 007) and higher ingestion of lean fish. Patients with lower body fat content had a higher milk intake (r=-0, 274;p=0, 001). Higher consumption of red meat was associated with higher muscle mass and protein content (r>0, 142;p<0, 033). We also found a relation between higher PTH and higher BMI (r=0, 310;p=0, 034). Conclusions: Patients that had a lower BMI and reduced body fat content consumed more lean fish, also those with lower body fat content showed a higher intake of milk. Red meat was associated with higher muscle mass and protein content. High PTH levels were correlated with higher BMI, which is in concordance with new evidence suggesting that overweight and obesity do not protect against OP. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5279